Clusters of starch-g-PCL and their effect on the physicochemical properties of films - Ramírez Hernández, Aurelio; Aparicio Saguilan, Alejandro; Mata-Mata, José L.; González-García, Gerardo; Hernández-Mendoza, Héctor; Báez-García, Eduardo; Conde Acevedo, Jorge Carlos (Starch - Stärke, 2017)
Starch-g-PCL films were prepared using the casting method and were characterized by different instrumental techniques and physicochemical properties. Nuclear magnetic resonance and Fourier transform infrared spectroscopy led to the proposal of a chemical structure for the films. The scanning electron microscopy (SEM) images of the films showed the formation of clusters of the graft copolymer starch-g-PCL. The effects of these clusters on the crystallinity (X-ray powder diffraction) revealed that the crystalline zones of the films increased by 46% and the elongation percentage increased by up to 50%. Also, the chemical degradation (aqueous hydrolysis) and the soil degradation of these films were 1.9 and 2.6 times faster than the films of starch alone. However, the thermal degradation temperature of the films decreased by more than 15°C, the moisture content decreased to 6.5%, and the water vapor permeation values increased in the films that contained starch-g-PCL. These results were accentuated with the increase in the amount of starch-g-PCL clusters.
Keywords: Almidón; Película biodegradable; Biodegradación